Drug Utilization Pattern During Flood Season In The State Of Kelantan, Malaysia: Perceptions, Experiences And Challenges In Military Field Hospitals - Yaacob, Mohammad Firdaus (2021)
Every medical mission faces a dilemma on which type of drugs to be brought adequately to cover the whole operation throughout the mission. There are uncertain-ties about the duration of mission, type of drugs to be brought, and difficulties in communication and land transport in the disaster area. Pharmacists will be able to plan which medical stock to bring if they can acquire relevant data regarding the pat-tern of drug utilization from previous missions. The deployment of a military field hospital for the purpose of responding to natural disaster, man-made conflicts, and peacekeeping mission, as well as conventional battlefield, brings grief challenges to healthcare providers. They face many uncertainties in different environments and situations, including the exposure to personal and health threats. This current re-search was conducted in two phases (mixed method: explanatory design). The first phase was a quantitative study, which was a retrospective and descriptive examina-tion of the drug utilisation pattern during the flood season of 2014 at a military field hospital which was deployed at Manek Urai, Kelantan. This study aimed to estimate the drug utilisation pattern during a specific flood season at a military field hospital in the state of Kelantan. The researcher analysed 2771 prescriptions with an average of 103 prescriptions per day. Most of the patients displayed diseases related to the respiratory system (44.9%); skin problem (15.1%); and the digestive system (11.6%).